Bobobox's Dedication To And Confidence In Its Customers Influences The Quality Of Service And Social Media Promotion - Doddy Adhimursandi (Cita Konsultindo Research Center, 2023)
Development technology information Which very fast No just change method consumer in shop, will but Also ways Which used by company For influence And guard loyalty consumer on product or service company. Objective from study This is For analyze influence satisfaction customer, quality service And promotion in media social to loyalty customer, Which mediated by commitment And trust on bobbox users. This research was conducted in September – December 2022 with spread questionnaire in a manner on line to respondent Which chosen with purposive sampling with a total of 117 people and PLS-SEM was used as a tool inference. Study This find that Satisfaction customer influential positive for commitment and trust, quality of service and promotion in the media social influential positive on trust, And commitment And trust capable mediate connection between Satisfaction customer, quality service, promotion on social media and loyalty customer.